2013
DOI: 10.1038/ejhg.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

A global map for dissecting phenotypic variants in human lincRNAs

Abstract: Large intergenic noncoding RNAs (lincRNAs) are emerging as key factors of multiple cellular processes. Cumulative evidence has linked lincRNA polymorphisms to diverse diseases. However, the global properties of lincRNA polymorphisms and their implications for human disease remain largely unknown. Here we performed a systematic analysis of naturally occurring variants in human lincRNAs, with a particular focus on lincRNA polymorphism as novel risk factor of disease etiology. We found that lincRNAs exhibited a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…200 nt that do not contain an open reading frame; although their biological meaning and function still need to be elucidated, ample evidence, including specific subcellular localization, tissue specificity, and association with disease, indicates that they may be essential regulators of cell function (27)(28)(29). The importance of lncRNAs in MS is highlighted by recent studies showing that various SNPs associated with MS in GWAS are located in genomic regions that code for lncRNAs (30) or regulate lncRNA expression in cis in human monocytes (31). Abundant expression of ANKRD55 007 in CD4 + T cells may be an indication of the unique cell-specific functional role for this noncoding RNA; it is an intriguing finding that merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…200 nt that do not contain an open reading frame; although their biological meaning and function still need to be elucidated, ample evidence, including specific subcellular localization, tissue specificity, and association with disease, indicates that they may be essential regulators of cell function (27)(28)(29). The importance of lncRNAs in MS is highlighted by recent studies showing that various SNPs associated with MS in GWAS are located in genomic regions that code for lncRNAs (30) or regulate lncRNA expression in cis in human monocytes (31). Abundant expression of ANKRD55 007 in CD4 + T cells may be an indication of the unique cell-specific functional role for this noncoding RNA; it is an intriguing finding that merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…47 A number of studies examined the implication of lincRNAs in complex diseases based on GWAS studies (LincPoly 48 , LincSNP 49 ). These studies represent initial efforts to integrate disease-associated SNPs and human lincRNAs, but both datasets do not include complete GWAS SNP data, and focus on only a few thousand lincRNAs.…”
Section: The Tools Of Functional Genomicsmentioning
confidence: 99%
“…For example, rs6475606, rs564398 and rs496892, rs1063192, and rs2151280 modify susceptibility to intracranial aneurysm, large-vessel ischemic stroke, glioma, and plexiform neurofibroma, respectively. Other correlations between lncRNA polymorphisms and disease are actively being investigated [79]. One study analyzed data from the Alzheimer Disease (AD) Neuroimaging Initiative and reported that the rs7990916:T> C polymorphism in the brain-specific, rapidly evolving lincRNA, TCONS_00021856/linc-SLITRK5-11, is associated with regional cortical gray matter volumes in normal controls and in patients with mild cognitive impairment and AD [80].…”
Section: Establishing Paradigms For Lncrna-related Pathologymentioning
confidence: 99%